Surface modification of a microfiltration membrane for enhanced anti-biofouling capability in wastewater treatment process. (December 2018) - Tse, Leda K.; Takada, Kazuki; Jiang, Sunny C.
Abstract: Membrane bioreactors (MBR) are now widely implemented in wastewater treatment plants due to their compact design and high effluent water quality. However, membrane biofouling has significant impact on MBR performance and energy cost. Quorum sensing inhibiting (QSI) compounds have the ability to disrupt bacterial communication pathways that lead to biofilm formation and biofouling. In this study, an anti-biofouling membrane was developed by incorporating vanillin, a known QSI molecule onto the surface of a commercial chlorinated polyethylene (CPE) microfiltration membrane by Williamson ether synthesis reaction. The CPE membrane was reacted with the vanillin in a solvent mixture containing potassium carbonate and N, N-dimethylformamide for vanillin incorporation. The solvent mixture without vanillin was also used to create a control membrane to understand the QSI anti-biofouling capabilities. Raman and FTIR spectroscopy indicated that vanillin was retained on the modified membrane surface under cross-flow condition and sodium hypochlorite cleaning. The modified membrane had significantly less biofouling compared to the unmodified and control membranes tested using activated sludge collected from wastewater treatment plants. The control membrane experienced up to a 52% reduction in live cells, dead cells, and polysaccharides in the fouling layer compared to unmodified membrane. The incorporation of vanillin further decreased the amount of live cells, dead cells, and polysaccharides covering the surface by 82%, 77%, and 51%, respectively, compared to the unmodified membrane. This research showed that vanillin-modified membranes have potential to improve the membrane anti-biofouling capabilities and MBR performance.